Ozone/Oxygen Molecules Exert Mild Oxidative Stress on Testis Mitochondria Isolated from the Rat Testicular Ischemia/Reperfusion Injury - Farshad Shahi; Shabnam Rahimi; Vahan Moradians; Nematollah Jonaidi Jafari; Morteza Izadi (Journal of Antioxidant Activity, 2022)
Testicular ischemia-reperfusion injury is an urgent situation which needs a timely and precise diagnosis for prevention of testis damages. Here in we investigated ozone/oxygen therapy in Testicular Ischemia/Reperfusion Injury. For this purpose, animals (rats) were divided to four groups; control, torsion/detortion, torsion/detortion + ozone/oxygen (30 µg/ml) and only ozone/oxygen. Four hours after detorsion, in all groups orchiectomy was done – for measuring the oxidative stress and mitochondrial toxicity parameters. Also, we preformed analysis of testicular spermatogenesis after 90 days. Our data showed that testicular torsion-detorsion induced significant increase in mitochondrial toxicity and decrease of spermatogenesis, malondialdehyde and GSSG levels were shown. Also, spermatogenesis, a remarkable decrease in malondialdehyde GSSG levels and mitochondrial toxicities were observed when compared with torsion-detorsion group. Obtained results for this research showed that ozone/oxygen therapy enhance antioxidant properties in the spermatogenic cells and protects testes from ischemia-reperfusion injury.
Keywords: Oxidative stress